2019
DOI: 10.1108/dat-10-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Severe alcohol withdrawal syndrome: review of the literature

Abstract: Purpose The purpose of this paper is to identify published literature from a general hospital setting that may highlight variables implicated in the development of severe alcohol withdrawal syndrome (SAWS) in patients who have alcohol dependence syndrome (ADS). Design/methodology/approach A systematic literature review was carried out using the electronic databases: MEDLINE, Medline in Process, Cinahl, Embase and PsycINFO from 1989 to 2017. The focus of this search was on English language studies of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…AWS spans a spectrum that ranges from mild and, in the most extreme circumstances, severe that includes DTs and ARS. However, the SAWS literature presents findings that are conflicting and inconclusive, prompting this study (Benson et al, 2019). Accounting for the limitations of the SAWS literature, in this analysis, we compared a group of patients who had ADS and developed SAWS or not in a randomly selected acute hospital population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AWS spans a spectrum that ranges from mild and, in the most extreme circumstances, severe that includes DTs and ARS. However, the SAWS literature presents findings that are conflicting and inconclusive, prompting this study (Benson et al, 2019). Accounting for the limitations of the SAWS literature, in this analysis, we compared a group of patients who had ADS and developed SAWS or not in a randomly selected acute hospital population.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic literature review carried out by the authors and published previously identified a number of flaws in the SAWS literature (Benson, Roberts, McCallum, & McPherson, 2019). The flaws included inconsistent data coding and databases that were not recognized or validated, which made it difficult to extrapolate to a wider population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to admit to hospital for alcohol detoxification is not supported by the lack of a tool to inform physicians in this decision (Benson et al, 2019;NICE, 2016;Stephens et al, 2014;Repper-DeLisi et al, 2008). Despite a number of retrospective studies investigating risk factors and SAWS, the only protocol located for the identification of low SAWS risk was developed by Stephens et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study and described in this paper is to investigate whether the GMAWS and the quantitative variables identified through a systematic literature review (Benson et al, 2019) can be used in the emergency department to help stratifying a person's risk of developing SAWS and support clinicians in their decision to admit or not. The variables were; previous SAWS, ARS, DT`s, hours since last drink, age, post code, gender, reason for admission, physical observations, blood results, co-morbidities, and level of ADS.…”
Section: Introductionmentioning
confidence: 99%